Exploring the English Language Comprehension, Reading Fluency, and Executive Functions of Spanish-English Bilingual Adolescents with Reading Difficulties. Issue 3 (4th May 2022) - Weaver, Andrew; Kieffer, Michael J.
Abstract: This study examines differences in English language comprehension, reading fluency, and executive functions among Spanish-English bilinguals with reading difficulties. Reading difficulties examined included general reading difficulties, defined by low word reading and reading comprehension, and specific-reading comprehension difficulties, defined by low reading comprehension yet adequate word reading. Participants ( N  = 86) were categorized using multiple measures of reading comprehension and word reading in each of 6th, 7th, and 8th grade. Participants were also categorized based on persistent difficulties (i.e. remaining in the same group across multiple grades). On two measures of language comprehension, readers with either difficulty tended to demonstrate significant weaknesses relative to average readers. On passage reading fluency, readers with specific-reading comprehension difficulties performed worse than average readers but better than readers with general reading difficulties. On executive functions, readers with general reading difficulties demonstrated weaknesses relative to average readers, but there was little evidence that readers with specific-reading comprehension difficulties showed these weaknesses. These findings typically held when looking at readers with persistently defined difficulties. Longitudinal analyses indicated that 47% of students with S-RCD and 56% of students with GRD remained in their group across the three years, consistent with prior research. Findings highlight potential weaknesses in executive functions for children with general reading difficulties that should be considered when designing instruction for these students. These findings also support prior research on the importance of developing English language and reading fluency for Spanish-English bilingual children with reading difficulties.